The English aristocracy : 1070-1272: a social transformation - Crouch, David (Yale University Press, 2011)
William the Conqueror's victory in 1066 was the beginning of a period of major transformation for medieval English aristocrats. In this groundbreaking book, David Crouch examines for the first time the fate of the English aristocracy between the reigns of the Conqueror and Edward I. Offering an original explanation of medieval society -- one that no longer employs traditional "feudal" or "bastard feudal" models -- Crouch argues that society remade itself around the emerging principle of nobility in the generations on either side of 1200, marking the beginning of the ancien regime. The book describes the transformation in aristocrats' expectations, conduct, piety, and status; in expressions of social domination; and in the relationship with the monarchy. Synchronizing English social history with non-English scholarship, Crouch places England's experience of change within a broader European transformation and highlights England's important role in the process. With his accustomed skill, Crouch redefines a fascinating era and the noble class that emerged from it. - Publisher